MicroRNA‐16 Is Downregulated During Insulin Resistance and Controls Skeletal Muscle Protein Accretion. Issue 8 (15th January 2016) - Lee, David E.; Brown, Jacob L.; Rosa, Megan E.; Brown, Lemuel A.; Perry, Richard A.; Wiggs, Michael P.; Nilsson, Mats I.; Crouse, Stephen F.; Fluckey, James D.; Washington, Tyrone A.; Greene, Nicholas P.
ABSTRACT: Insulin resistant diabetes, currently at epidemic levels in developed countries, begins in the skeletal muscle and is linked to altered protein turnover. microRNAs downregulate targeted mRNA translation decreasing the amount of translated protein, thereby regulating many cellular processes. Regulation of miRNAs and their function in skeletal muscle insulin resistance is largely unexplored. The purpose of this study was to identify the effects of insulin resistance on contents of skeletal muscle miRNAs with potential functions in protein turnover. We examined miRs ‐1, ‐16, ‐23, ‐27, ‐133a, ‐133b, and ‐206 in muscles of Zucker rats. miR‐1 was 5‐ to 10‐fold greater in obesity, whereas miRs‐16 and ‐133b were repressed ∼50% in obese compared to lean rats, with no other alterations in miRNA contents. miR‐16 correlated to protein synthesis in lean, but not obese rats. miR‐16 reduction by lipid overload was verified in ‐ vivo by diet‐induced obesity and in ‐ vitro using a diacylglycerol analog. A role for miR‐16 in protein turnover of skeletal myocytes was established using transient overexpression and anti‐miR inhibition. miR‐16 overexpression resulted in lower protein synthesis (puromycin incorporation, ∼25–50%), mTOR (∼25%), and p70S6K1 (∼40%) in starved and insulin stimulated myoblasts. Conversely, anti‐miR‐16 increased basal protein synthesis (puromycin incorporation, ∼75%), mTOR (∼100%), and p70S6K1 (∼100%). Autophagy was enhanced by miR‐16 overexpression (∼50% less BCL‐2, ∼100% greater LC3II/I, ∼50% less p62) and impaired with miR‐16 inhibition (∼45% greater BCL‐2, ∼25% less total LC3, ∼50% greater p62). This study demonstrates reduced miR‐16 during insulin resistance and establishes miR‐16 control of protein accretion in skeletal muscle. J. Cell. Biochem. 117: 1775–1787, 2016. © 2015 Wiley Periodicals, Inc. Abstract : microRNAs control various cellular processes in many different tissues types and hold great potential as a target for therapeutics. Insulin resistance downregulates the amount of miR‐16 in skeletal muscle and by controlling levels of miR‐16 in muscle cells, the synthesis and autophagic degradation of protein can be altered.